Clinical study of wearable low-intensity pulsed ultrasound treatment in the improvement of executive function in obesity (the SLITE trial): protocol for a single -centre, double-blind, randomized controlled trial - Xiong, Xiaoxian; Zhong, Chuanyu; Zhang, Tingyu; Xie, Xue; Hao, Junnian; Zheng, Yuanyi; Liu, Fengjing (Frontiers in Human Neuroscience, 2025)
IntroductionObesity is a global health crisis associated with significant physical and cognitive impairments, particularly in executive function. Impaired executive function exacerbates unhealthy eating behaviors and hinders effective weight management. Non-invasive neuromodulation techniques like transcranial direct current stimulation and transcranial magnetic stimulation have demonstrated potential in improving executive function and assisting in weight reduction but face limitations in accessibility and efficacy. Low-intensity pulsed ultrasound (LIPUS) represents an emerging neuromodulation technique distinguished by its non-invasive application and superior spatial resolution, facilitating targeted modulation of cortical activity and neural excitability with high precision. This study aims to explore the efficacy of LIPUS on executive function in obesity.Methods and analysisThis study adopts a prospective, single-center, double-blind, randomized controlled design. A total of 44 participants diagnosed with obesity (BMI ≥ 28 kg/m2) will be enrolled and equally assigned to the LIPUS and sham groups. The LIPUS group will receive pulsed therapeutic ultrasound for 4 weeks, while the sham group will receive placebo treatment using a device delivering no therapeutic ultrasound. Both groups will undergo assessments at baseline and after 4 weeks, with the primary outcome being the change in reaction time on the food Go/No-go task. Secondary outcomes include changes in body weight, BMI, food cravings (measured by the Food Craving Questionnaire-Trait and State versions), food-eating behavior (measured by the Visual Analog Scale and the Dutch Eating Behavior Questionnaire), and cognitive performance as assessed by the Stroop test. Additional neuroimaging assessments will include functional near-infrared spectroscopy (fNIRS), functional magnetic resonance imaging (fMRI), and electroencephalography (EEG).DiscussionThis trial will be the first to evaluate LIPUS for enhancing executive function in individuals with obesity. By combining wearable ultrasound technology with neuroimaging assessments, the study is expected to provide novel evidence for the neuromodulatory role of LIPUS. The results may support the development of innovative, non-invasive strategies for obesity management and inform future clinical applications.